Productivity and Organizational Management - Broncano, Santiago Gutierrez; Davim, J. Paulo; Elmas, Emin Taner; Ferreira, Ana Paula; Machado, Carolina, 1965-; Nedelko, Zlatko; Oliveira, Teresa Carla; Suryanarayana, A. (De Gruyter, 2017)
Effective work practices and good employee relations are a real necessity of nowadays organizations, as they can help to reduce absenteeism, turnover, organizational costs, conducting to high levels of commitment, effectiveness, performance as well as productivity. Addressing these questions, this book focuses on the implications of changes in productivity and organizational management, exploring models, tools and processes.